Thermospheric wind and temperature observations from El Leoncito Observatory in southern South America - Martinis, C.; Meriwether, J. W.; Navarro, L. A. (Frontiers in Astronomy and Space Sciences, 2025)
A Fabry–Perot interferometer (FPI) installed at El Leoncito Observatory, Argentina (31.8o S, 69.3o W, 18o mag lat), provides data on neutral winds and temperature over southern South America, a region lacking ground-based thermospheric observations. We present the climatology of neutral winds obtained from 630.0 nm airglow emissions. Results are shown for different seasons and different levels of solar activity. Temperature results are shown only for medium-to-high solar activity conditions. The modeled neutral winds show better agreement during high solar activity conditions. The modeled temperatures underestimate the observed values and do not reproduce the midnight temperature maximum observations. These observations will help improve model predictions of thermospheric parameters for this region.